Cushing's syndrome - Findling, James W; Raff, Hershel (Saunders, 2005)
This issue covers the gamut of endocrine disorders in the pediatric and adolescent patient population, including vitamin D deficiency and rickets, idiopathic short stature, polycystic ovary syndrome, obesity, regulation and disorders of onset of puberty, diabetes, hypoglycemia, and thyroid cancer. A must for endocrinologists treating children and adolescents.
Endocrinology and metabolism clinics of North America, ISSN 0889-8529 vol. 34, no. 2, June 2005
Keywords: Cushingův syndrom; Cushing Syndrome; neurologie; endokrinologie; glukokortikoidy; Glucocorticoids